Bartholin’s Abscess with Bacterial Vaginosis Coinfection Successfully Treated with a Modified Word Catheter and Combined Antibiotics - Santo, Nugrah; Muhlis, Muhlis; Iswanty, Muji; Idrus, Idrianti; Massi, Nasrum (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Bartholin’s abscess is an infection of the Bartholin gland that often occurs in women of childbearing age. The prevalence of Bartholin’s abscess is 2% in the female population worldwide. Patients often complain dyspareunia with a high recurrence rate. Bacterial Vaginosis (BV) is a syndrome of changes in the vaginal ecosystem that occurs spontaneously in sexually active women. BV can contribute to the development of a Bartholin’s gland abscess. CASE REPORT: A 30-year-old woman came with the chief complaint of a 5 cm × 5 cm erythematous, tender, and mobile mass on the right side of the labia majora. In addition, the patient also experienced recurrent vaginal discharge. The patient was diagnosed with Bartholin’s abscess with BV coinfection that was successfully treated with a modified word catheter and combination of antibiotics that showed no recurrence. CONCLUSION: Combination of modified word catheter and antibiotics can be a simple yet effective way in treating Bartholin’s abscess.